EFEKTIFITAS PEMBIAYAAN MUDARABAH/MUSYARAKAH DALAM MENINGKATKAN KINERJA BANK PERKREDITAN RAKYAT SYARIAH DI PROVINSI BANTEN - Badina, Tenny; Rosiana, Rita; Ahyakudin, Ahyakudin (ALQALAM, 2017)
The purpose of this research is to analyze the effect of the distribution of mudarabah/musyarakah financing to the performance of mudarabah/musyarakah financing in Sharia Rural Bank Banten Province as well as to build a model of mudarabah/musyarakah financing that is effective in improving the performance of Sharia Rural Bank in Banten Province. The research method used is survey method with quantitative approach with multiple regression analysis. Hypothesis testing using SPSS v.17 software. Data collection techniques used are documentation, survey, and interviews. The population of this research is all the leaders and staff of financing in Banten Province, with 40 samples. The results showed that the variables of Third Party Fund Mobilization, Minimizing Dependence on Subsidies, Incentive System for On-Time Payments, and Building Good Relationships with Customers have a significant positive effect on the Mudarabah/Musyarakah Financing Performance, while the Selection Process and Control Process on Business variables have no effect on Mudarabah/Musyarakah Financing Performance. Keywords: Sharia Rural Bank, Mudarabah/Musyarakah Financing, Effectiveness, Performance